The Role of Firearms in Violence Scripts : The Dynamics of Gun Events among Adolescent Males - Fagan, Jeffrey (Law and contemporary problems, 1996)
In recent years, the use and deadly consequences of gun violence among adolescents has reached epidemic proportions. At a time when national homicide rates are declining, the increasing rates of firearm deaths among teenagers is especially alarming. Deaths of adolescents due to firearm injuries are disproportionately concentrated among nonwhites, and especially among African-American teenagers and young adults. Only in times of civil war have there been higher within-group homicide rates in the United States. There appears to be a process of self-annihilation among male African-American teens in inner cities that is unprecedented in American history. Unfortunately, few studies have examined these sharp increases in gun fatalities among young males. This article attempts to contribute to the scant literature by examining the role of firearms in violent events among adolescent males. First, using an event-based approach, it suggests a framework for explaining interactions that involve adolescents and firearms. Events are analyzed as situated transactions, including rules that develop within specific contexts, the situations where weapons are used, the motivations for carrying and using weapons, and the personality sets of groups where weapons are used. There are rules that govern how disputes are settled, when and where firearms are used, and the significance of firearms within a broader adolescent culture. This approach does not deny the importance of the individual attributes that bring people to situations, but it recognizes that once in the situation, other processes shape the outcomes of these events